The Northernmost Volcanoes in South America (Colombia, 5–6°N): The Potentially Active Samaná Monogenetic Volcanic Field - Sánchez-Torres, Laura; Murcia, Hugo; Schonwalder-Ángel, Dayana (Frontiers in Earth Science, 2022)
The northernmost volcanism in South America (5 – 6 °N) is defined by the presence of several monogenetic edifices, which have been grouped within the Samaná Monogenetic Volcanic Field. Few volcanoes have been studied so far and now they are recognised as a cluster of volcanoes of intermediate to acid composition, formed by both explosive and effusive eruptions. This paper presents the geological characterisation of the Samaná Field through petrography, mineral chemistry, whole-rock geochemistry, geochronological analyses and geothermobarometric calculations. The analyses indicate that the field is formed by at least seven volcanoes. Mineralogically, the erupted products host plagioclase (An26-74) and amphibole (magnesiohastingsite, tschermakite and mangesiohornblende) as the most abundant phases, although orthopyroxene (enstatite; Wo2-3 En70-76 Fs21-28) and clinopyroxene (diopside and augite; Wo44-45, En41-42, Fs13-15 and Wo42-44, En46-47, Fs10-11, respectively) also appear. Less abundant phases like olivine (Fo81-88), biotite (magnesiobiotite), quartz and Fe-Ti oxides (Usp4-89 Mag96-11 and Ilm61-92 Hem39-8) were also recognised. Chemically, the volcanoes are of andesitic to dacitic composition with calc-alkaline affinity, and show similar behaviour of LILE, HFSE and REE, which is typical for magmatism in subduction environments. Ages yield a range between 1.32 ± 0.06 Ma (K/Ar) and 16,919 ± 220 years (14C), which indicates that it is a relative long-lived volcanic field and that it is potentially active. The results also indicate that the volcanoes share a common magmatic source that fed the individual eruptions and that the magma differentiation is mainly controlled by processes of fractional crystallisation, although evidence of magma recharge processes or magma mixing and assimilation as a minor process are also recognised. Geothermobarometric calculations suggests that the different mineral crystallised between 1194 – 687 °C and 0.88 – 0.19 GPa. This indicates the above-mentioned processes occurred not only at the main magmatic reservoir (~33 – 21 km) but also at different stagnation zones at shallower levels of the crust (~7 – 5 km). Taking this into account, we show that the magmas evolution of this monogenetic field is more complex than individual batches of magma reaching the surface uninterrupted, as it is normally described for monogenetic volcanic fields of more mafic compositions.